Straining to define a healthy microbiome - Anna M. Seekatz (mSphere, 2025)
ABSTRACT In 2020, I wrote an mSphere of Influence commentary on two studies that shaped my research perspective on the human gut microbiome (McNulty et al., Sci Transl Med 3:106ra106, 2011, https://doi.org/10.1126/scitranslmed.3002701; Hamilton et al., Gut Microbes 4:125, 2013, https://doi.org/10.4161/gmic.23571). The microbiome field has continued to progress since the publication of these studies over 10 years ago, emerging as a considerable factor in almost all areas focused on disease development. My previous commentary highlighted two areas that piqued my interest early on in my career: (i) that the extant microbial community should be considered when proposing to manipulate the microbiota, such as via probiotics or fecal microbiota transplantation, and (ii) that realized (i.e., transcribed) functional changes of the microbiota may occur independent of changes in its composition. Since writing that commentary, two microbiota-based therapeutics for the treatment of Clostridioides difficile infection have been approved, highlighting the potential success of using the microbiota to treat or prevent disease. Despite these wins and ever-growing evidence of the importance of the microbiome in managing our health, translating mechanistic studies into therapeutic value has been slower. In this minireview, I expand upon two large questions that would increase our ability to translate the microbiome into therapies, highlighting both historical and recent progress.